Higher internal locus of control is associated with higher performance in a workplace walking intervention, Global Corporate Challenge® - Haoxiong Sun; Pei-Chun Ko; S. Fiona Barker; Danijela Gasevic; Jessica Stone; Rosanne Freak-Poli (PLoS ONE, 2026)
Background Given the increasing reliance on self-regulation in modern work environments, understanding how psychological characteristics influence physical activity participation can help inform more effective health promotion strategies. This study examines whether individuals with different Locus of Control (LOC) orientations show varying levels of engagement and performance in a workplace pedometer program. Methods We conducted a secondary analysis of 426 office workers in Melbourne, Australia who participated in the 2008 Global Corporate Challenge® (GCC®), a four-month team-based pedometer program encouraging 10,000 steps per day. Internal LOC (ILOC) was assessed at baseline, four months, and 12 months using the Duttweiler Internal Control Index. Baseline ILOC was the primary exposure. Program performance was operationalized as average daily step counts and achievement of the 10,000-step daily goal. Linear regression and logistic regression, adjusted for workplace clustering and covariates, were used to examine associations between ILOC and outcomes. Paired t-tests and descriptive comparisons were used to assess changes in ILOC over time. Results Participants with higher baseline ILOC were older (p < 0.001), more likely to have previously completed the GCC® (p = 0.039), more health-motivated (p = 0.015), met fruit (p = 0.040) and vegetable (p = 0.003) intake guidelines, and reported higher wellbeing and mental health-related quality of life (both p < 0.001). During the program, higher ILOC was associated with higher average daily step counts (β = 46.97, 95% CI [24.62, 69.33]; p = 0.001) and greater likelihood of achieving the 10,000-step goal (OR = 1.02, 95% CI [1.01, 1.03]; p = 0.001). ILOC showed no significant net change overall, but a clear regression-to-the-mean pattern was observed across baseline quartiles. Conclusions Higher ILOC was associated with better performance in the pedometer program, though this did not translate into sustained additional health gains.